2010
DOI: 10.1517/14656566.2010.522567
|View full text |Cite
|
Sign up to set email alerts
|

Sumatriptan therapy for headache and acute myocardial infarction

Abstract: Inherent in its mechanism of action, sumatriptan could produce (coronary) vasospasm sometimes followed by AMI. The drug should not be prescribed to patients with history, symptoms or signs of ischemic vascular disease; an in-depth evaluation should be carried out in subjects at intermediate cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 95 publications
1
12
0
1
Order By: Relevance
“…Several of the migraine abortive therapies, particularly triptans and ergot alkaloids, have vasoconstrictive effects that may predispose individuals to ischemic events. [31] However, large population studies have not found an increased risk of adverse vascular events among migraineurs using triptan therapy. [3233] Medication overuse, however, may be more problematic.…”
Section: Why Are Migraine and Stroke Comorbid Conditions?mentioning
confidence: 99%
“…Several of the migraine abortive therapies, particularly triptans and ergot alkaloids, have vasoconstrictive effects that may predispose individuals to ischemic events. [31] However, large population studies have not found an increased risk of adverse vascular events among migraineurs using triptan therapy. [3233] Medication overuse, however, may be more problematic.…”
Section: Why Are Migraine and Stroke Comorbid Conditions?mentioning
confidence: 99%
“…This class of medications inhibits the release of vasoactive peptides and promotes vasoconstriction, combating the pathologic vasodilatation contributing to migraine headaches. 1 Potential complications of these vasoconstrictive properties include myocardial infarction, 2 , 3 cerebrovascular accident, 4 ischemic colitis, 5 and spinal cord infarction. 6 We present a case of bilateral renal infarctions associated with sumatriptan use.…”
Section: Introductionmentioning
confidence: 99%
“…3 The arterial vasoconstriction is enhanced when endothelial function is impaired as it is, for example, in smokers. 3 The arterial vasoconstriction is enhanced when endothelial function is impaired as it is, for example, in smokers.…”
Section: Expert Commentarymentioning
confidence: 99%